Production and validation of a booklet on intestinal ostomy care for colorectal cancer patients - Vieira Rocha, Letícia Ellen; Monteiro de Oliveira, Filipe; Matheus Alves Fernandes, Helder; Bandeira, Rodrigo Lima; Leite Cavalcante, Marcelo; Barreto, Andrezza Silvano; Cavalcante, Viviane Mamede Vasconcelos; Coelho, Manuela de Mendonça Figueirêdo (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To produce and validate an educational booklet on intestinal ostomy care for patients with colorectal cancer. Method: A methodological study conducted in three stages: literature review, production of the booklet, and content and appearance validation by experts using the Content Validity Index (CVI). A convenience sample was utilized. Contact was made electronically, where the booklet and an assessment instrument containing 21 questions were sent, covering: objective, content, relevance, figures, writing style, and organization. The specialists evaluated whether items were: highly adequate, adequate, partially adequate, or totally inadequate. The study was approved by the Ethics Committee. Results: The booklet titled "Intestinal Ostomy Care" consists of 22 pages and 37 illustrations. The content addressed: colorectal cancer; care of the collection equipment; oncological treatment; social rights; psychological aspects; nutritional aspects; and physical activity. Twelve specialists responded. All 21 items were considered valid (CVI > 0.70); of these, 16 had a CVI = 1, 3 had a CVI = 0.9167, and 1 had a CVI = 0.75. Conclusion: The booklet was considered valid. The validation process provided the material with the methodological rigor necessary for its use in scientific environments and patient guidance. However, clinical validation with the target audience is suggested.